PENGARUH PERSONALITY DAN KEMAMPUAN KERJA KARYAWAN TERHADAP KEPUASAN TAMU PADA HOTEL GRAND SURYA KEDIRI - Prasastono, H. Ndaru (Proceeding SENDI_U, 2015)
This research was conducted to test and analyze the influence of personality and ability to work on guestsatisfaction at Grand Surya Hotel Kediri either partial or simultaneously, and examine which variablesare dominant influence. The method used in this study is an explanatory method, the research is takingplace Grand Surya Hotel Kediri in October and November, with a sample of 80 hotel guests who stay,data collection techniques such as observation, questionnaires, interviews and literature.The results ofdata analysis showed that partially personality affect guest satisfaction with a standardized betacoefficient of 0.538, while the ability to affect the job satisfaction of the guests with a standardized betacoefficient of 0.396. While simultaneously indicated by the coefficient of determination adjusted R Squareof 0.784, meaning that the variable personality and ability to work are able to explain 78.4% change inguest satisfaction, while 21.6% is influenced by other variables outside of the study. Thus, personalityvariables, and the ability to work has an influence on guest satisfaction Grand Surya Hotel Kediri.Keywords: personality, ability to work, and guest satisfaction.